Estudio del desamargado por lavado tradicional de dos Ecotipos, dos variedades de chocho (Lupinus mutabilis Sweet) y dos índices de madurez. - Lema Quinatoa, Fanny Margoth (2021)
This research aimed to carry out a study of debittering by traditional washing of two ecotypes, two varieties of lupine (Lupinus mutabilis Sweet) and two maturity indices. It was proposed an experimental design of a factorial arrangement Ax B x C under a completely randomized block design (DBCA), where the factors such as Factor A (Varieties of lupine and Ecotypes), Factor B (time and temperature of 40 min. 94 °C), Factor C (Maturity Index) obtained 24 treatments. For the statistical analysis of the data obtained, it was carried out through the Infostat program, where it was determined that the best treatment compared to the control treatment was t12 (INIAP Variety 451 Guaranguito + time and temperature of 40 min. 94 °C + Maturity Index in dry) with a pH of 6, 12%, moisture 75, 45%, ash 1.92%, alkaloids 0.03%, they comply with the requirements of the Ecuadorian Technical Standard NTE INEN 2390 Unmarried chocho. It was concluded that the best variety is the INIAP 451 Guaranguito variety, at a debittering time and temperature of 40 min. 94 ° C in the dry maturity index since they are statistically significant with respect to obtaining the debittered lupine and an added value was given to the best variety combining with the local Peruvian Ecotype 1, to give agri-food alternatives.